High-performance PVA/functionalized graphene oxide nanocomposite membranes for direct methanol fuel cells - D.M. Sobhy; Asmaa Attya Shalaby; Randa Eslah Khalifa; Yehia A. El-Taweel; Taghreed Mohamed Mohamed Zewail; F. Shokry (Results in Engineering)
This study aimed to synthesized economically and cost-effective polyelectrolyte membranes using cross-linked poly (vinyl alcohol)/glutaraldehyde. Phosphorylated graphene oxide (PGO) was created through phosphorylating graphene oxide (GO) with phosphoric acid (PA). The structural properties of PGO were characterized using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and Thermogravimetric analysis (TGA). Following this, GO/PGO was incorporated into crosslinked PVA to manufacture composite membranes using the solution casting method. These membranes demonstrated exceptional thermal stability, remarkable mechanical properties, favorable water absorption, and enhanced proton conductivity. The physicochemical characteristics of the nanocomposite membranes, including ion exchange capacity, solvent absorption, mechanical stability, methanol permeability, and proton conductivity, were assessed. The PVA composite membrane containing 3.5 wt.% of PGO exhibited superior tensile strength (36.5∓2.8MPa), reduced methanol permeability (4.14×10−7 cm 2/S) and exceptional proton conductivity (7.6 mS·cm−1 at 25 °C), surpassing both crosslinked PVA and PVA/GO composite membranes. The results revealed that the addition of 3.5 wt.% PGO improves mechanical strength, IEC and protonic conductivity that reached 36.5 MPa, 2.09 mmol/g and 7.6 mS/cm, respectively. Single-cell estimation using PVA/PGO-3.5 % membrane demonstrated a maximum power density of 36.5 mW.cm⁻² at 30 °C. These findings increase the viability of PVA/PGO-3.5 % polyelectrolytic membranes for PEMFC application. The findings suggest the potential for developing an affordable proton exchange membrane suitable for direct methanol fuel cell (DMFC) applications.